2001
DOI: 10.1002/jso.1057
|View full text |Cite
|
Sign up to set email alerts
|

Clear cell sarcoma: The Roswell Park experience

Abstract: CCSTA is an aggressive tumor of the soft tissues. Early recognition and management are associated with an excellent long-term prognosis. Tumors greater than 5 cm warrant aggressive surgical management and treatment, and are at high risk of the development of distant disease. Aggressive multiagent chemotherapy appeared to have no impact on outcome. Other adjuvant therapeutic options including immunotherapy should be investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
65
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(69 citation statements)
references
References 30 publications
3
65
1
Order By: Relevance
“…4 -8 Follow-up studies have shown that approximately 55% of patients die of their disease within 5 years after diagnosis. 5,7,8 Since CCS displays a number of histopathologic features that overlap with conventional malignant melanoma, there may be difficulties in the distinction between CCS and metastatic malignant melanoma with an unknown primary site. 2,9 Clonal chromosomal abnormalities have been described in 25 CCSs, and the translocation t(12;22)(q13;q12-13), detected in 17 of the cases, appears to be a characteristic rearrangement.…”
mentioning
confidence: 99%
“…4 -8 Follow-up studies have shown that approximately 55% of patients die of their disease within 5 years after diagnosis. 5,7,8 Since CCS displays a number of histopathologic features that overlap with conventional malignant melanoma, there may be difficulties in the distinction between CCS and metastatic malignant melanoma with an unknown primary site. 2,9 Clonal chromosomal abnormalities have been described in 25 CCSs, and the translocation t(12;22)(q13;q12-13), detected in 17 of the cases, appears to be a characteristic rearrangement.…”
mentioning
confidence: 99%
“…Some previous reports have described the use of either chemotherapy or radiotherapy for treating clear cell sarcoma. However, the response rate to chemotherapy was 0-25% in these reports and the 5-year overall survival rate ranged from 55 to 68%, so these treatments had little impact [12][13][14][15][16] (Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…However, melanoma only very rarely presents with a soft tissue metastasis in the absence of a detectable skin or mucous membrane tumor. In addition, the t(12;22)(q13;q12) translocation is pathognomonic of clear cell sarcoma of soft tissues; it does not occur in melanoma [5,7]. A clear cell sarcoma can occur at any age but predominantly affects female patients aged between 20 and 40 years [3,5,7,15].…”
Section: Discussion and Treatmentmentioning
confidence: 99%
“…In addition, the t(12;22)(q13;q12) translocation is pathognomonic of clear cell sarcoma of soft tissues; it does not occur in melanoma [5,7]. A clear cell sarcoma can occur at any age but predominantly affects female patients aged between 20 and 40 years [3,5,7,15]. Over 95% of all clear cell sarcomas are located in the extremities, with the foot and ankle affected in approximately 40% [3,4,7].…”
Section: Discussion and Treatmentmentioning
confidence: 99%
See 1 more Smart Citation